Fermentative Butanol Production—Perspectives and Scale-Up Challenges - Seedhabadee Ganeshan; Mehmet Çağlar Tülbek (Encyclopedia)
Sustainable solutions to the use of petrochemical products have been increasingly sought after in recent years. While alternatives such as biofuels have been extensively explored and commercialized, major challenges remain in using heterogeneous feedstocks and scaling-up processes. Among biofuels, higher alcohols have recently gained renewed interest, especially in the context of upcycling agri-food residues and other industrial organic wastes. One of the higher alcohols produced via fermentation is butanol, which was developed over a century ago. However, the commercial production of butanol is still not widespread, although diverse feedstocks are readily available. Hydrolysis of the feedstocks and scale-up challenges in the fermentation and purification of butanol are recurring bottlenecks. This review addresses the current state of fermentative butanol production and opportunities to address scale-up challenges, including purification. With the significant interest and promise of precision fermentation, this review also addresses some of the recent advances and potential for enhanced fermentative butanol production.